The role of auditing in achieving sustainable performance of external development funds in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to shed light on the cognitive framework of the concept of auditing and the importance and recognition of the importance and impact of sustainability and its three dimensions (environmental, economic and social) on the performance of the Iraq Fund for External Development And studying the impact of auditing on sustainable performance A set of financial indicators were used to achieve the research objectives, including profitability and liquidity indicators to achieve the economic dimension, in addition to using growth and innovation indicators to achieve the social and environmental dimension, and statistical analysis was used to measure the correlation R between international auditing standards and their consistency with the evaluation of the sustainable performance of the Iraq Fund for External Development for the period from 2018-2022 The research concluded that the current law governing the work of the fund has become out of step with the changes occurring in the surrounding environment, and that there is a prominent role for oversight and auditing in improving the institution's operations and adding value to it, in addition to the benefits resulting from improving internal control activities, risk management and governance rules.